1986
DOI: 10.1080/14640748608401616
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Working Memory

Abstract: This study explored the hypothesis that patients suffering from dementia of the Alzheimer type (DAT) are particularly impaired in the functioning of the Central Executive component of working memory, and that this will be reflected in the capacity of patients to perform simultaneously two concurrent tasks. DAT patients, age-matched controls and young controls were required to combine performance on a tracking task with each of three concurrent tasks, articulatory suppression, simple reaction time to a tone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
384
5
5

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 605 publications
(420 citation statements)
references
References 15 publications
22
384
5
5
Order By: Relevance
“…Impaired levels of performance have been observed in elderly subjects on divided attention paradigms (Inglis & Caird, 1963;McDowd & Craik, 1988;Salthouse, Rogan, & Prill, 1984;Tun et aI., 1991;Wright, 1981). However, many studies have also failed to observe age differences in divided attention (e.g., Baddeley, Logie, Bressi, Della Sala, & Spinnler, 1986;Belleville, Malenfant, et aI., 1992;Somberg & Salthouse, 1982;Wickens, Braune, & Stokes, 1987). The discrepancy observed here might relate to the failure of previously used paradigms to control for the processing requirement of the individual tasks.…”
Section: Resultscontrasting
confidence: 53%
“…Impaired levels of performance have been observed in elderly subjects on divided attention paradigms (Inglis & Caird, 1963;McDowd & Craik, 1988;Salthouse, Rogan, & Prill, 1984;Tun et aI., 1991;Wright, 1981). However, many studies have also failed to observe age differences in divided attention (e.g., Baddeley, Logie, Bressi, Della Sala, & Spinnler, 1986;Belleville, Malenfant, et aI., 1992;Somberg & Salthouse, 1982;Wickens, Braune, & Stokes, 1987). The discrepancy observed here might relate to the failure of previously used paradigms to control for the processing requirement of the individual tasks.…”
Section: Resultscontrasting
confidence: 53%
“…Evidence for the characteristics of the central executive is accumulating, and its role as coordinator of the slave systems has empirical support (Baddeley, Bressi, Della Sala, Logie, & Spinnler, 1991;Baddeley, Logie, Bressi, Della Sala, & Spinnler, 1986). A similar concept has arisen in studies ofdivided attention where this function is referred to as a cost ofconcurrence (Navon & Gopher, 1979) or as an executive time sharer (Hunt & Lansman, 1982;McLeod, 1977;Moray, 1967;Yee, Hunt, & Pellegrino, 1991).…”
Section: Working Memorymentioning
confidence: 99%
“…These studies have compared the performance of AD patients and normal elderly subjects in tasks investigating one specific aspect of executive function. Some of these studies (Baddeley, Logie, Bressi, et al, 1986;Baddeley, Bressi, Della Sala, et al, 1991;Nestor, Parasuman, & Haxby, 1991) used a dual-task paradigm and found that AD patients were particularly impaired when they had to perform simultaneously two different tasks, even when the difficulty of the tasks performed separately was equated across the groups. Such a difficulty to co-ordinate two tasks was also present when subjects do not have to store presented information.…”
Section: Introductionmentioning
confidence: 99%